42‐2: Invited Paper: OptRod: A Shape‐Free and Multi‐Functional Display System Operated by Projected Images. Issue 1 (30th May 2018) - Itoh, Yuichi; Shirai, Ryo; Ueda, Shori; Fukamachi, Taichi; Yamashita, Mayu; Onoye, Takao
Abstract : In this paper, we propose OptRod, a shape‐free and multi‐functional display system operated by projected images. A PC generates images as control signals and projects them to the bottom of OptRods by a projector or LCD. An OptRod receives the light and converts its brightness into a control signal for the attached output device. By using multiple OptRods, the PC can simultaneously operate many output devices without any signal lines. Moreover, we can arrange surfaces of various shapes easily by combining multiple OptRods. OptRod supports various functions by replacing the device unit connected to OptRod.